2014
DOI: 10.1155/2014/307950
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydial Infection and Its Role in Male Infertility

Abstract: Introduction.Chlamydia trachomatisis an established cause of tubal factor infertility; however its role in male fertility is not as clear. We sought to determine the prevalence of Chlamydia in infertile men and evaluate its impact on male reproductive potential.Materials and Methods. We compared the incidence of Chlamydia in our infertile male population with that reported in the literature. We then reviewed the impact of Chlamydia infection on male fertility.Results. The incidence of Chlamydia infection in ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 109 publications
1
7
1
Order By: Relevance
“…Because PCR diagnostic method is the most sensitive test for the detection of C. trachomatis and L. monocytogenes, in the current study the presence of these two bacteria in semen specimens of infertile men was assessed using this method. In a study conducted by Samplaski and colleagues on infertile men using the PCR assay at Toronto's Mount Sinai Hospital, the presence of C. trachomatis was estimated to be about 0.3% (34). The prevalence of C. trachomatis reported in the aforementioned studies is lower than the current study.…”
Section: Discussioncontrasting
confidence: 73%
“…Because PCR diagnostic method is the most sensitive test for the detection of C. trachomatis and L. monocytogenes, in the current study the presence of these two bacteria in semen specimens of infertile men was assessed using this method. In a study conducted by Samplaski and colleagues on infertile men using the PCR assay at Toronto's Mount Sinai Hospital, the presence of C. trachomatis was estimated to be about 0.3% (34). The prevalence of C. trachomatis reported in the aforementioned studies is lower than the current study.…”
Section: Discussioncontrasting
confidence: 73%
“…There are significant variations in the prevalence of C. trachomatis infections in men with infertility ranging from 0% to 42.3%, depending on the methodology, type of sample and differences of infection rates in different populations. In a recently published Canadian study16 the prevalence of C. trachomatis infection in 5588 infertile men, was 0.3%. The author concluded that this low prevalence clearly demonstrates that a small proportion of male infertility is caused by C. trachomatis 17…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, in some literature it has been reported that Chlamydia trachomatis affects semen quality. These contradictory results could be due to the different methodologies and techniques used, which can be difficult to compare [36,37].…”
Section: Chlamydia Trachomatismentioning
confidence: 99%